A comparison of outcomes for patients with intermediate and high risk prostate cancer treated with low dose rate and high dose rate brachytherapy in combination with external beam radiotherapy. (January 2020) - Slevin, Finbar; Rodda, Sree Lakshmi; Bownes, Peter; Murray, Louise; Bottomley, David; Wilkinson, Clare; Adiotomre, Ese; Al-Qaisieh, Bashar; Dugdale, Emma; Hulson, Oliver; Mason, Joshua; Smith, Jonathan; et al.
Highlights: Superior biochemical progression free survival for LDR in combination with EBRT. On multivariable analysis, HDR and EBRT and Gleason ≥8 predicted for progression. Low cumulative incidence of ≥grade 3 GU and GI toxicities. Abstract: Introduction: There is evidence to support use of external beam radiotherapy (EBRT) in combination with both low dose rate brachytherapy (LDR–EBRT) and high dose rate brachytherapy (HDR–EBRT) to treat intermediate and high risk prostate cancer. Methods: Men with intermediate and high risk prostate cancer treated using LDR–EBRT (treated between 1996 and 2007) and HDR–EBRT (treated between 2007 and 2012) were identified from an institutional database. Multivariable analysis was performed to evaluate the relationship between patient, disease and treatment factors with biochemical progression free survival (bPFS). Results: 116 men were treated with LDR-EBRT and 171 were treated with HDR–EBRT. At 5 years, bPFS was estimated to be 90.5% for the LDR–EBRT cohort and 77.6% for the HDR–EBRT cohort. On multivariable analysis, patients treated with HDR–EBRT were more than twice as likely to experience biochemical progression compared with LDR–EBRT (HR 2.33, 95% CI 1.12–4.07). Patients with Gleason ≥8 disease were more than five times more likely to experience biochemical progression compared with Gleason 6 disease (HR 5.47, 95% CI 1.26–23.64). Cumulative incidence of ≥grade 3 genitourinary and gastrointestinal toxicities for the LDR–EBRT and HDR–EBRT cohorts were 8% versus 4% and 5% versus 1% respectively, although these differences did not reach statistical significance. Conclusion: LDR–EBRT may provide more effective PSA control at 5 years compared with HDR–EBRT. Direct comparison of these treatments through randomised trials are recommended to investigate this hypothesis further.